Autism interest intensity in early childhood associates with executive functioning but not reward sensitivity or anxiety symptoms. (October 2022) - Godfrey, Kate J; Espenhahn, Svenja; Stokoe, Mehak; McMorris, Carly; Murias, Kara; McCrimmon, Adam; Harris, Ashley D; Bray, Signe
Several theories have been proposed to explain the presentation of intense interests in autism, including theories based on altered executive functioning, imbalanced reward sensitivity, and mitigating anxiety. These theories have yet to be examined in early childhood, yet knowledge of how intense interests emerge could provide insight into how best to manage intensity and support the many benefits of personal interests. Parents of 33 autistic and 42 non-autistic comparison children aged 3–6 years completed questionnaires to assess attention shifting and inhibitory control, responsiveness to rewards, and anxiety symptoms. Each behavior domain was examined for associations with parent-reported interest intensity. In autistic and comparison children, attention shifting was associated with interest intensity, where children with more difficulties showed more intense interests. In autistic children only, inhibitory control of attention also associated with interest intensity, where children with greater difficulties showed more intense interests. Reward and anxiety symptoms did not associate with interest intensity in either group, or across the sample. These findings suggest that, in early childhood, the presentation of intense interests is related to executive functioning regardless of diagnostic group. Helping children develop executive functioning skills may therefore be useful to assist with managing interest intensity in early childhood. Lay abstract: Personal interests in autism are a source of joy, pride, and assist with the formation of social relationships. However, highly intense engagement can also interfere with other activities including activities of daily living. Theories have suggested that intense interests relate to executive functioning, reward sensitivity, and anxiety symptoms; but none of these theories have been tested in early childhood. Understanding which behavioral traits relate to intense interests in early childhood could help understand how intense interests may emerge, while also providing clues for how to manage interest intensity and best promote the many benefits of personal interests. We recruited families with autistic and non-autistic children aged 3–6 years. Parents completed questionnaires to assess children's interest diversity and intensity, executive functioning, reward sensitivity, and anxiety symptoms. We found that for autistic and non-autistic children, greater difficulty shifting attention between activities related to more intense interests. In autistic children only, difficulty with inhibitory control of attention also related to more intense interests. However, reward sensitivity and anxiety symptoms did not relate to interest intensity. Based on these observations, assisting young children with developing executive functioning skills could help with mediating the interference of interests in daily life to ultimately promote the many benefits of personal interests.